Salivary Glycine Is a Significant Predictor for the Attenuation of Polyp and Tumor Microenvironment Formation by Fucoxanthin in AOM/DSS Mice - TERASAKI, MASARU (In Vivo, 2019)
Background/ Aim: A high polar xanthophyll of Fucoxanthin (Fx) is abundantly contained in edible brown algae, and it has chemopreventive effects in mouse cancer models, however, the underlying mechanisms of these effects are not well understood. Thus, we aimed to investigate the effects of Fx on the tumor microenvironment in cancer model mice. Materials and Methods: We investigated the effect of Fx (30 mg/kg body weight) in a variety of cell types within the tumor microenvironment of α mouse preclinical colorectal cancer model and analyzed the mouse saliva in search of predictors for cancer chemopreventive effects. Results: Fx administration significantly decreased the number of colorectal polyps and tended to decrease colonic lesions compared to untreated control mice. In addition, Fx administration showed significantly lower numbers of colorectal cancer stem cells-like CD44(high)/EpCAM(high )cells, cancer-associated fibroblasts-like αSMA(high )cells, tumor-associated macrophages-like and dendritic cells-like CD206(high )cells by 0.6-, 0.5- and 0.6-fold, respectively, compared to untreated control mice. Moreover, the treatment also showed significantly lower levels of salivary glycine by 0.5-fold. Conclusion: Our results suggest that salivary glycine may be a predictor representing the chemopreventive effect of Fx in mice.